3D Printing of Dual‐Cure Networks Based on (Meth)acrylate/Bispropargyl Ether Building Blocks. Issue 7 (13th October 2022) - Sommer, Katharina; Rieger, Paul; Müller, Stefanie Monika; Schwarz, Romana; Trimmel, Gregor; Feuchter, Michael; Griesser, Thomas
Abstract : In recent years, dual‐cure chemistry has been exploited to realize interpenetrating networks (IPNs) that provide enhanced thermo‐mechanical properties. In this contribution, photoinduced curing of (meth)acrylates is used to build the desired 3D structure, whereas the thermally triggered polymerization reaction of 2H‐chromene functionalized building blocks is utilized to create the IPN. This strategy combines the advantages of traditional UV‐curable monomers with high‐performance thermosets. After the successful synthesis of the bispropargyl ether derivative, i.e., 4, 4′‐(propane‐2, 2‐diyl)bis((ethynyloxy)benzene), its thermally induced conversion to the corresponding 2H chromene functionalized prepolymer is studied by Fourier‐transform infrared spectroscopy and gel permeation chromatography. The network formation as well as the printability of various formulations containing different amounts of the thermo‐curable building block is investigated. The obtained IPNs provide enhanced thermo‐mechanical properties making these resins suitable for the additive manufacturing of functional 3D parts for high‐performance applications. Abstract : This work deals with the exploration of a photoreactive dual‐cure resin system based on (meth)acrylates and bispropargylether building blocks for lithography‐based additive manufacturing. Photoinduced curing of (meth)acrylates builds the desired 3D structure, whereas thermally triggered polymerization reaction of 2H‐chromene functionalized monomers forms the interpenetrating network. The obtained photopolymers exhibit improved thermomechanical properties, making these materials suitable for high‐performance applications.